Endotoxin, extracellular polysaccharides, and β(1‐3)‐glucan concentrations in dust and their determinants in four European birth cohorts: results from the HITEA project. (21st December 2012) - Casas, L.; Tischer, C.; Wouters, I. M.; Valkonen, M.; Gehring, U.; Doekes, G.; Torrent, M.; Pekkanen, J.; Garcia‐Esteban, R.; Hyvärinen, A.; Heinrich, J.; Sunyer, J.
Abstract Early‐life exposure to microbial agents may play a protective role in asthma and allergies development. Geographical differences in the prevalence of these diseases exist, but the differences in early‐life indoor microbial agent levels and their determinants have been hardly studied. We aimed to describe the early‐life levels of endotoxin, extracellular polysaccharides (EPS), and β(1‐3)‐glucans in living room dust of four geographically spread European birth cohorts (LISA in Germany, PIAMA in the Netherlands, INMA in Spain, and LUKAS2 in Finland) and to assess their determinants. A total of 1572 dust samples from living rooms of participants were analyzed for endotoxin, Penicillium/Aspergillus EPS, and β(1‐3)‐glucans. Information on potential determinants was obtained through questionnaires. Concentrations of endotoxin, EPS, and β(1‐3)‐glucans were different across cohorts. Concentrations of endotoxin and EPS were respectively lower and higher in INMA than in other cohorts, while glucans were higher in LUKAS2. Season of sampling, dog ownership, dampness, and the number of people living at home were significantly associated with concentrations of at least one microbial agent, with heterogeneity of effect estimates of the determinants across cohorts. In conclusion, both early‐life microbial exposure levels and exposure determinants differ across cohorts derived from diverse European countries.